Demonstration of Aqueous Reprocessing of U-Zr and U-Pu-Zr Metallic Alloy Fuels Using an Ejector Mixer-settler with Tri-n-Butyl Phosphate (TBP) as the Extractant. Issue 3 (16th April 2021) - Sreenivasulu, B; Rajeswari, S.; Suresh, A.; Sivaraman, N.
ABSTRACT: U-Zr and U-Pu-Zr metallic alloy fuels have been employed in fast reactors in the early days and these fuels have been considered for use in future fast reactors in India. It is proposed to develop an aqueous method based on the PUREX process for the reprocessing of spent metallic fuels. In the present study, an ejector mixer-settler was employed to demonstrate the feasibility of aqueous reprocessing of U-Zr and U-Pu-Zr metallic alloy fuels with tri-n-Butyl Phosphate (TBP) as the extractant. Continuous counter-current mixer settler runs were separately carried out with U-Zr and U-Pu-Zr feed solutions using 1.1 M TBP/n-DD solvent. Quantitative extraction of U and U + Pu was achieved within five stages leaving zirconium in the raffinate in the case of U-Zr and U-Pu-Zr feed solutions, respectively. Quantitative back extraction of uranium from loaded organic phase was achieved using 0.01 M HNO3 in the case of U-Zr mixer-settler runs. Dual strip solutions such as 2 M and 0.01 M HNO3 were used for the quantitative stripping of U and Pu from the loaded organic phase in the case of U-Pu-Zr mixer-settler runs. The proposed flow sheets demonstrate that the aqueous reprocessing of metallic fuels using a PUREX-based method is feasible.